Evaluation of mining - manufacturing enterprises using financial indicators - Stehlíková Beáta (Acta Montanistica Slovaca, 2002)
One of dimensions of enterprise results objectiveness is the arrangement of the enterprise into the "space". The paper deals with theoretical and practical aspects of such space determination, based on financial indicators of created enterprises for this purpose from mining and manufacturing industry enterprises. The financial indicators, if they are "read out right", present precious information to subjects interested in. Moreover, the financial indicators reflect a particular sector; from the historical standpoint, specific financial indicators mirror signs characteristic for individual stages of economy (in this period it is the market economy transformation process), as well as some specifics of the accounting system.